Effects of air temperature on COVID-19 case fatality rate - Anna Sączewska-Piotrowska; Damian Piotrowski (Contemporary Economics, 2021)
The aim of this study was to assess the case fatality rate (CFR) of COVID-19 by performing a metaanalysis according to the air temperature and to determine if the temperature modifies the pandemic duration to the peak day for CFR of the COVID-19. A novel coronavirus spread began in December 2019 in Wuhan, China, and half a year after, more than 9 million total cases were confirmed worldwide. Therefore, knowing the conditions favorable for the spread of the virus (including weather conditions) is crucial from the perspective of the entire population. Using information from the World Health Organization, subgroup meta-analysis by temperature was performed. Survival analysis using the Kaplan-Meier estimates and the Cox proportional hazards models was conducted. Based on the conducted analysis we can conclude that in countries with temperature equal or lower than 14.8êC the pooled CFR of COVID-19 is higher than in countries with temperature greater than 14.8êC. Besides, in countries with lower temperature the peak of the CFR appears after a longer time from the first case of the novel coronavirus than in countries with higher temperature.
Keywords: C41; J19; J10; 330; Case fatality rate; COVID-19; meta-analysis; survival analysis; air temperature